Порівняльна оцінка рістстимулювальної активності екстрактів ехінацеї блідої (Echinacea pallida (Nutt.) Nutt.) та препарату “Циркон” - Buydin, V.V.; Pospelov, S.V.; Samorodov, V.M.; Buydin, O.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
For the first time in the laboratory the effect of extracts (roots, leaves, inflorescences) pale coneflower (Echinacea pallida (Nutt.) Nutt.) at concentrations of 0.1%, 0.01% and 0.001% on the germination of barley’s caryopsis in comparison with a known stimulant Zircon from purple coneflower (Echinacea purpurea (L.) Moench) was investigated. It is established that at temperature 15 degrees above zero extracts of pale coneflower have growth-stimulating activity. This is manifested in increased root length and coleoptile test object, and their wet weight.